2015
DOI: 10.4103/2230-8598.165087
|View full text |Cite
|
Sign up to set email alerts
|

Substance use among adolescents living in slums of Guwahati city, Assam: A growing public health concern

Abstract: Introduction: Substance use has been a menace throughout the world for several centuries, and adolescents seem to be the most vulnerable group and the miasma of the slums adds to this multi-dimensional problem. Objectives: To study the prevalence and pattern of substance use among adolescents living in slum of Guwahati. Materials and Methods: A cross-sectional study was conducted among the adolescents living in slums of Guwahati, Assam, India during February to May 2014. Out of the total 90 slums, 23 slums wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…(9) Bardhan T et al (2015) in their study in Guwahati, Assam found 83.4% prevalence of gutka use and Kamate RP et al (2017) in their study in Belagavi, Karnataka observed 78.87% prevalence of smokeless tobacco which were higher than the present study finding. (10), (11) Prevalence of ever users and current users of khaini in the present study were found to be 8.7% and 6.2% respectively. Studies done by Bhaskar RK et al and Bardhan T et al found the prevalence of khaini use among adolescents to be 9.2% and 9.7% respectively, which were consistent with the present study finding.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…(9) Bardhan T et al (2015) in their study in Guwahati, Assam found 83.4% prevalence of gutka use and Kamate RP et al (2017) in their study in Belagavi, Karnataka observed 78.87% prevalence of smokeless tobacco which were higher than the present study finding. (10), (11) Prevalence of ever users and current users of khaini in the present study were found to be 8.7% and 6.2% respectively. Studies done by Bhaskar RK et al and Bardhan T et al found the prevalence of khaini use among adolescents to be 9.2% and 9.7% respectively, which were consistent with the present study finding.…”
Section: Discussionsupporting
confidence: 41%
“…Studies done by Bhaskar RK et al and Bardhan T et al found the prevalence of khaini use among adolescents to be 9.2% and 9.7% respectively, which were consistent with the present study finding. (9), (10) Khaini use is an age-old practice among the tea garden population of Assam. The tea garden workers use it while they pluck tea leaves in the gardens.…”
Section: Discussionmentioning
confidence: 99%